Incidence and outcome of invasive candidiasis in intensive care units (ICUs) in Europe: results of the EUCANDICU project - Bassetti, Matteo; Dubler, Simon (Critical care, 2019)
Background: The objective of this study was to assess the cumulative incidence of invasive candidiasis (IC) in intensive care units (ICUs) in Europe. Methods: A multinational, multicenter, retrospective study was conducted in 23 ICUs in 9 European countries, representing the first phase of the candidemia/intra-abdominal candidiasis in European ICU project (EUCANDICU). Results: During the study period, 570 episodes of ICU-acquired IC were observed, with a cumulative incidence of 7.07 episodes per 1000 ICU admissions, with important between-center variability. Separated, non-mutually exclusive cumulative incidences of candidemia and IAC were 5.52 and 1.84 episodes per 1000 ICU admissions, respectively. Crude 30-day mortality was 42%. Age (odds ratio [OR] 1.04 per year, 95% CI 1.02–1.06, p < 0.001), severe hepatic failure (OR 3.25, 95% 1.31–8.08, p 0.011), SOFA score at the onset of IC (OR 1.11 per point, 95% CI 1.04–1.17, p 0.001), and septic shock (OR 2.12, 95% CI 1.24–3.63, p 0.006) were associated with increased 30-day mortality in a secondary, exploratory analysis. Conclusions: The cumulative incidence of IC in 23 European ICUs was 7.07 episodes per 1000 ICU admissions. Future in-depth analyses will allow explaining part of the observed between-center variability, with the ultimate aim of helping to improve local infection control and antifungal stewardship projects and interventions.